Unilateral complete ureteral duplication with distal ureteral stone: A rare entity - Karakose, Ayhan; Aydogdu, Ozgu; Atesci, Yusuf Ziya (Canadian Urological Association Journal, 2013)
Complete duplex ureters opening separately into the urinary bladder is extremely rare; they can be embryologically explained as a development of two ureteral buds separately from a single mesonephric duct. We describe a case of unilateral complete ureteral duplication with distally localized ureteral stone in a 49-year-old male who presented with right flank pain.